Bringing justice to habitat conservation with Indigenous refugia: potential for planning and management of Douglas-fir (Pseudotsuga menziesii var. glauca) in New Mexico - Hausam, Sharon (Frontiers in Sustainability, 2024)
In the face of climate change and associated increases in disturbances, some areas, known as refugia, will remain or become newly habitable for species, while others will be lost. Planning and managing for refugia can support biodiversity and conservation, and could also integrate climate justice for Indigenous communities, framed as recognition, procedural, and distributional justice. However, without explicit consideration of justice, planning and management for refugia risks unnecessarily limiting information about local conditions and traditional practices that may be contained in Indigenous knowledges, and causing maladaptive consequences such as exclusion of Indigenous communities from decision-making and from newly protected areas, with and loss of use of traditional plants and animals, which can have negative impacts on Indigenous communities' cultural and social well-being. The article proposes a new concept, Indigenous refugia, that incorporates three types of justice into existing theories of refugia for conservation in the face of climate change: recognition justice as understanding and respect for Indigenous values, experiences, and knowledges; procedural justice in collaboration and decision-making; and distributional justice as access to species and lands that sustain cultural and social processes. It presents a potential example of Indigenous refugia for the for integration of justice principles into planning and management of refugia for climate-vulnerable Douglas-fir in New Mexico in collaboration with Pueblo, Diné (Navajo), Nde (Apache), and other Indigenous peoples with ancestral lands in the area.